A Conceptual Framework for Designing a Computer-based Dyslexia Screening Test - Fatma Susilawati, Mohamad; Mokhairi, Makhtar; Syadiah Nor, Wan Shamsuddin; Rohayah, Husain (2014)
Dyslexia is a type of specific learning disability that affects people of all backgrounds globally without prejudice. Most learning institutions applied paper-based screening tools to identify dyslexic children before they are referred to psychologists for further tests to identify the students’ disabilities. The advantages of computer based applications in healthcare have been well established. Moreover, previous researches in computer-based screening tests are limited and innovations are poorly designed to be used by dyslexics. This paper is a conceptual framework for the development of a Computer-based Dyslexia Screening Test (CDST). The framework consists of assessment modules (for the purpose of screening dyslexia) and proposed design guidelines specifically for dyslexic children. The assessment modules and design guidelines were specially formulated to detect dyslexia at an early stage. CDST is expected to act as an early detection dyslexia screening tool without the children knowing that they are being screened.